Educational priorities of low-and middle-income country medical diaspora organisations: A critical discourse analysis. - Ishrat Hussain; Lois Haruna-Cooper; Sharon Isiramen; Nina van der Mark; Mishal Khan; Mohammed Ahmed Rashid (Public Library of Science (PLoS), 2024)
Rising global migration levels have led to growing diaspora populations. There has been interest in the role of diaspora healthcare professionals (HCPs) from low- and middle-income countries (LMICs) in development aid to their origin countries, although there has been comparatively less focus on their educational activities. This study examined the stated educational priorities of LMIC medical diaspora organisations, with a particular focus on the tension between promoting professional opportunities afforded by medical migration and contributing to healthcare workforce shortages due to migration away from LMICs.We gathered a textual archive from webpages and public documents of 89 LMIC medical diaspora organisations in high income countries, predominantly the US and UK. We employed Foucauldian critical discourse analysis to examine presented rationales around educational policies and practices, with a focus on encouragement towards, and discouragement from, medical migration. Two discourses dominated this archive. The first was of preservation and framed the educational work of these organisations as a means of providing unity and social networks to diaspora HCPs, with a focus on maintaining their cultural identity and heritage, and medical connections with their origin countries. The second was of aspiration and framed their educational work as providing support to diaspora HCPs to advance their careers and maximise training opportunities, often through directly enabling and supporting migration to high income countries. There was a discursive absence around brain drain with no policies or practices that overtly sought to deter against, or offset the negative effects of, medical migration. Notwithstanding the valuable contributions that LMIC medical diaspora organisations make in global health, the discursive framings that shape their educational work are linked primarily to protecting and progressing diaspora HCPs rather than on LMIC workforce challenges. Further research is needed to examine potential impacts of these positions on HCP migratory behaviours.